(untitled) (Archaeologia Adriatica, 2026)
Fieldwork carried out on Vis in 2022 and 2024 has made it possible to supplement existing understanding of its network of prehistoric settlements and their functions, as well as the island’s social dynamics. Surveys of the Grodac and Štracine sites enabled a revision of previous interpretations. At Grodac, the boundaries of the hillfort area were defined more precisely, while at Štracine the previous hypothesis of a hillfort settlement was revised. Analysis of portable material provided new evidence of trade exchange between indigenous communities and the Greeks during the Iron Age, and the chronological framework of certain sites was also refined. The field survey of prehistoric cairns and hillforts identified systems of visual communication between key points, which allowed strategic control over land and maritime routes.